Cellulose nanofiber/elastomer composites with high tensile strength, modulus, toughness, and thermal stability prepared by high-shear kneading. (1st March 2020) - Noguchi, Toru; Endo, Morinobu; Niihara, Kenichi; Jinnai, Hiroshi; Isogai, Akira
Abstract: An aqueous TEMPO-oxidized cellulose nanofiber (TOCN) dispersion and aqueous hydrogenated acrylonitrile-butadiene rubber (H-NBR) latex were mixed with or without applying high shear forces. The TOCN/H-NBR mixtures containing TOCN volume ratios of 0–10.0% were then converted to crosslinked composite sheets with peroxide between the H-NBR molecules by hot-pressing. When the aqueous TOCN/H-NBR mixtures were pretreated with high shear forces, the crosslinked TOCN/H-NBR composites exhibited concomitant high tensile strength, high tensile modulus, high ductility, high storage modulus, and high dimensional stability to temperature. These properties are better than those of H-NBR composites containing single-walled carbon nanotubes or carbon black at the same filler volume ratio. In the crosslinked TOCN/H-NBR comosites prepared with high shear fodrces as pretreatment, electron microscopy images showed that the TOCN elements were homogeneously dispersed in the H-NBR matrix without forming aggregates. Thermal and pulsed NMR analyses of the solvent-extracted residue of the non-crosslinked TOCN/H-NBR composite indicated that characteristic nanostructures formed in the TOCN/H-NBR interfacial phases, which may cause the excellent mechanical and thermal properties of the composite. Graphical abstract: Image 1